Polynomial Chaos-Kriging metamodel for quantification of the debonding area in large wind turbine blades - Pavlack, Bruna [UNESP]; Paixão, Jessé [UNESP]; da Silva, Samuel [UNESP]; Cunha, Americo; García Cava, David (SAGE Publications, 2021)
This study aims to investigate the performance of a data-driven methodology for quantifying damage based on the use of a metamodel obtained from the Polynomial Chaos-Kriging method. The investigation seeks to quantify the severity of the damage, described by a specific type of debonding in a wind turbine blade as a function of a damage index. The damage indexes used are computed using a data-driven vibration-based structural health monitoring methodology. The blade’s debonding damage is introduced artificially, and the blade is excited with an electromechanical actuator that introduces a mechanical impulse causing the impact on the blade. The acceleration responses’ vibrations are measured by accelerometers distributed along the trailing and the wind turbine blade. A metamodel is formerly obtained through the Polynomial Chaos-Kriging method based on the damage indexes, trained with the blade’s healthy condition and four damage conditions, and validated with the other two damage conditions. The Polynomial Chaos-Kriging manifests promising results for capturing the proper trend for the severity of the damage as a function of the damage index. This research complements the damage detection analyses previously performed on the same blade.
Keywords: damage features; damage quantification; data-driven metamodel; Polynomial Chaos-Kriging; Structural health monitoring; wind turbine blades